2012
DOI: 10.1007/s00268-012-1768-9
|View full text |Cite
|
Sign up to set email alerts
|

Do Hernia Operations in African International Cooperation Programmes Provide Good Quality?

Abstract: The standard quality of surgery for the treatment of hernia in developing countries with few instrumental means, and in sub-optimal surgical conditions is similar to that provided in Spain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 40 publications
2
26
1
Order By: Relevance
“…Of 4,100 operations for cleft lip and palate by 1 organization in 40 simultaneous sites, for example, only 703 patients (17 %) returned for a 6- to 9-month postoperative visit [19]. Similarly, in a Spanish-African cooperation program for the repair of hernias, follow-up was 21 % [16]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 4,100 operations for cleft lip and palate by 1 organization in 40 simultaneous sites, for example, only 703 patients (17 %) returned for a 6- to 9-month postoperative visit [19]. Similarly, in a Spanish-African cooperation program for the repair of hernias, follow-up was 21 % [16]. …”
Section: Resultsmentioning
confidence: 99%
“…Finally, teams that aim to establish residency or training programs have yet to publish enough of their outcomes to be evaluated. The few papers that have been published are, however, promising [16, 17]. …”
Section: Introductionmentioning
confidence: 99%
“…Of the groups we analyzed all (100%) reported that patients were evaluated preoperatively. However, one paper describes how the preoperative evaluation consisted of only vitals and a glucometer [54]. Many papers simply did not specify the nature of their evaluations.…”
Section: Selection Preoperative Evaluation and Preparationmentioning
confidence: 99%
“…However, it still stands that the community of surgical STMMs is largely underrepresented in the literature as previously discussed. At the moment, we expect that those surgical STMMs who are not writing papers for publication are using a quantitative rather than qualitative measure of success, the aforementioned "body count method" [11,54]. Small surgical STMM organizations are not exposed to the scrutiny that medical mission moguls such as Operation Smile and Médecins Sans Frontières must face on the international stage [9].…”
Section: Outcome Measuresmentioning
confidence: 99%
See 1 more Smart Citation